Therapeutic Potential of Progranulin in Hyperhomocysteinemia-Induced Cardiorenal Dysfunction. Issue 2 (February 2017) - Fu, Yi; Sun, Yu; Zhou, Meng; Wang, Xiaojie; Wang, Ziying; Wei, Xinbing; Zhang, Yan; Su, Zeyu; Liang, Kaili; Tang, Wei; Yi, Fan
Abstract : Hyperhomocysteinemia (hHcys) is an important independent risk factor for the development of cardiovascular disease and end-stage renal disease. Although multiple approaches lowering the levels of homocysteine have been used in experimental studies and clinical trials, there is no effective therapy available to fully prevent homocysteine-induced injury. Therefore, identifying key molecules in the pathogenic pathways may provide clues to develop new therapeutic strategies for the treatment of hHcys-associated injury beyond lowering the plasma homocysteine levels. In this study, we found that the levels of progranulin (PGRN), an autocrine growth factor, were significantly reduced in the kidney and heart from a mouse model of hHcys. We further observed that in hHcys, PGRN-deficient mice significantly exacerbated cardiorenal injury as evidenced by higher levels of urinary albumin excretion, more severe renal morphological injuries, including pronounced glomerular basement membrane thickening and podocyte foot process effacement, and adverse myocardial remodeling versus wild-type mice. Mechanistically, we found that PGRN-medicated Wnt/β-catenin signaling was one of the critical signal transduction pathways that links homocysteine to cardiorenal injury. Importantly, we finally provided direct evidence for the therapeutic potential of PGRN in mice with hHcys by pretreatment with recombinant human PGRN. Collectively, our results suggest that PGRN may be an innovative therapeutic strategy for treating patients with hHcys. Abstract : Supplemental Digital Content is available in the text.